Transcriptome-Wide Analysis Reveals the Role of PPARγ Controlling the Lipid Metabolism in Goat Mammary Epithelial Cells - Hengbo Shi; Wangsheng Zhao; Changhui Zhang; Khuram Shahzad; Jun Luo; Juan J. Loor (PPAR Research)
To explore the large-scale effect of peroxisome proliferator-activated receptor γ (PPARG) in goat mammary epithelial cells (GMEC), an oligonucleotide microarray platform was used for transcriptome profiling in cells overexpressing PPARG and incubated with or without rosiglitazone (ROSI, a PPARγ agonist). A total of 1143 differentially expressed genes (DEG) due to treatment were detected. The Dynamic Impact Approach (DIA) analysis uncovered the most impacted and induced pathways “fatty acid elongation in mitochondria,” “glycosaminoglycan biosynthesis-keratan sulfate,” and “pentose phosphate pathway.” The data highlights the central role of PPARG in milk fatty acid metabolism via controlling fatty acid elongation, biosynthesis of unsaturated fatty acid, lipid formation, and lipid secretion; furthermore, its role related to carbohydrate metabolism promotes the production of intermediates required for milk fat synthesis. Analysis of upstream regulators indicated that PPARG participates in multiple physiological processes via controlling or cross talking with other key transcription factors such as PPARD and NR1H3 (also known as liver-X-receptor-α). This transcriptome-wide analysis represents the first attempt to better understand the biological relevance of PPARG expression in ruminant mammary cells. Overall, the data underscored the importance of PPARG in mammary lipid metabolism and transcription factor control.